New records and range expansion for Paspalum procurrens and P. volcanense in northwestern Argentina and southeastern Bolivia - Glücksberg, Adriana (2019)
Fil: Glücksberg, Adriana. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Botánica del Nordeste; Argentina.